A new limit for the NW Río de la Plata Craton Border at about 24°S (Argentina) detected by Magnetotellurics - Favetto, Alicia Beatriz (2015)
Old South American structures constitute a puzzle where the Río de la Plata Craton is the most important clue in the assembly of SW Gondwana. The present study is aimed at characterizing the western border of the Río de la Plata Craton on the basis of magnetotelluric studies. Magnetotelluric (MT) data were acquired along an approximately NW-SE 750km profile at about 24ºS, from the Sub-Andean Ranges in the province of Salta (NW) to the Formosa Province frontier (SE) next to Paraguay River. Distortion and structure dimensionality analysis indicates that MT responses are two-dimensional with a NS strike orientation, consistent with the regional geological strike. A 2-D inversion of the data provided a model showing a lateral discontinuity, possibly associated with cratonic structures. The high resistivity observed (>5000ohm·m), from about the middle of the profile toward its eastern end, may be interpreted as the terranes accreted to the Río de la Plata Craton during Neoproterozoic to Cambrian times, or as the Río de la Plata Craton itself. Along the profile from the surface to a depth of about 10km the resistivity model shows a significant resistivity variation in the structure. The resistive block identified at the western end of the profile represents the Sub-Andean system. The markedly enhanced low-resistivity structure (~1 to 10ohm·m) corresponds to a sedimentary pile whose thickness decreases from NW to SE.